American cutaneous leishmaniasis cases in the metropolitan region of Manaus, Brazil: association with climate variables over time (Geospatial Health, 2015)
A temporal series of the normalized difference vegetation index (NDVI) and other environmental parameters covering the years 2002- 2009 was used for the study of the potential association between the climate and the number of cases of American cutaneous leishmaniasis (CL) in Manaus Metropolitan Region (MMR), State of Amazonas, Brazil. The results show that CL has a marked seasonality and a strong linkage with local climate conditions. Dry and warm conditions favor the vector, while the maximum number of CL cases occurs during the following wet season. This has a clear relation to the El Niño/La Niña Southern Oscillation (ENSO) and the results presented here show that uncharacteristic dry conditions in the MMR follow El Niño after a lag period of 3 months, while wet conditions follow La Niña, again after a lag period of 3 months. El Niño brings dry conditions with warming of the land surface leading to increased growth of trees and bushes as indicated by rising NDVI values, eventually producing increased numbers of CL cases, with a peak of new cases occurring 4 to 5 months later. La Niña, on the other hand, produces wet and cool weather, which is less favorable for the leishmaniasis vector and therefore results in comparatively lower number of CL cases. Since these seasonal climate changes affect the dynamics of the CL vector, and thus the number of CL cases, a close watch of the ENSO phenomenon and the weather type it brings should be useful for monitoring and control of CL in the MMR.